Evaluación de la calidad bacteriológica del agua potable y pozos rústicos del caserío de Santa Clara de Nanay - Loreto - Vargas Rios de Orbe, Gritli Del Pilar (2016)
Worldwide, unsafe water consumption has caused approximately 1.8 million deaths from gastrointestinal infections. In addition, it has been estimated that 88% of diarrheal diseases are the result of an unhealthy water supply, poor sanitation and poor hygiene. In the Loreto region, population growth, both in rural and urban areas, has led to an increase in of the demand for water from surface and underground sources for human consumption. This growth is responsible at the same time for new sources of pollution, such as those from agricultural activities and inadequate wastewater management. The samples of rustic wells presented values of 88 / 100ml for total coliforms and 18.9 / 100ml for fecal coliforms, the percentage of total coliforms was 83.7% and fecal coliforms of 24.3%. The levels of total coliforms and fecal coliforms, indicate that the waters of the village of Santa Clara de Nanay, exceed the maximum permissible limits for these bacteria; while the samples of drinking water indicate the absence of aerobic mesophilic bacteria and the group of coliforms, this due to the preventive treatment that the JASS (Administrative Board of Service and Sanitation) performs to the drinking water before being distributed through the supply of home networks. In the present study, the bacteriological quality of the drinking water and rustic wells of the Santa Clara de Nanay farm was evaluated according to the reference values established in the General Water Law and the Standard of drinking water, in addition to qualifying the waters of the hamlet under study, comparing its degree of bacteriological contamination with the reference values established in the General Water Law and the Standard for Drinking Water.